Front Cover: Radicals and Anions of Siloles and Germoles (Chem. Eur. J. 47/2021). Issue 47 (6th July 2021) - Reinhold, Crispin R. W.; Schmidtmann, Marc; Tumanskii, Boris; Müller, Thomas
Abstract : The synthesis of sterically hindered persistent sila‐ and germacyclopentadienyl radicals adds magnetic properties to these heterocyclic ring systems and sparks the idea of their possible application as building blocks for molecular magnets (pictured as red‐blueish northern light). Support comes from the analysis of the EPR spectroscopic parameters and of their computed spin density ‐ shown here for the silicon species ‐ that indicate localization of the unpaired electron at the heteroatom. More information can be found in the Full Paper by B. Tumanskii, T. Müller, et al. (DOI: 10.1002/chem.202101415 ).